Małżeństwa, rozwody i wzrost gospodarczy - Baranowski, Paweł; Sztaudynger, Jan Jacek (Annales. Etyka w Życiu Gospodarczym, 2019)
The aim of the study is to estimate the impact of the so-called family social capital (family ties capital) on economic growth. We hypothesise that marital dissolution expresses decrease in the capacity for cooperation, collaboration and sharing responsibility not only within the family but also on a professional level. Thus, an increase in the divorce to marriage rate is accompanied by a slowdown in economic growth. The divorce rate is regarded here as an indirect cause of the slowdown. The reasons stem from the breakdown of cooperation and collaboration, as well as increased risk, trust reduction, and the shortening of the decision-making time horizon accompanying divorces and resulting from divorces. These phenomena directly affect the working members of the family in which a divorce takes place. According to the main hypothesis, their impact is transferred to professional life and concerns employee teams. For the study, we employ econometric models, the first one for Poland and the second for 15 European Union countries, for the period 1993–2017.